Magnetic Fe3S4 LTMCs micro-flowers@ wax gourd aerogel-derived carbon hybrids as efficient and sustainable electromagnetic absorber. (July 2021) - Pan, Fei; Liu, Zhicheng; Deng, Baiwen; Dong, Yanyan; Zhu, Xiaojie; Huang, Chuang; Shi, Zhong; Lu, Wei
Abstract: As a dielectric loss-type absorber, lamellar transitional metal chalcogenides (LTMCs) become more and more popular in the electromagnetic (EM) absorbing field due to their unique two-dimensional sheet structure. However, it remains challenging for metallic sulfides to obtain magnetic loss, further promoting loss mechanism. Herein, magnetic Fe3 S4 LTMCs micro-flowers@ wax gourd aerogel-derived carbon composites are fabricated through a facile pyrolysis process and subsequent hydrothermal method. Compared to a pure biomass carbon or Fe3 S4, Fe3 S4 @C composites exhibited an optimized and adjustable EM characteristic, which can be put down to the synergistic effects between the dielectric/magnetic loss and the impedance match. The sample shows superior EM absorption properties with a minimum reflection loss (RL) of −58.85 dB at 3.1 mm and a broad effective bandwidth (EBW) of 5.40 GHz at the matching thickness of 2.0 mm with a filling ratio of 20 wt%. In addition, the radar cross section (RCS) simulation confirms that the material can effectively suppress EMW (−8.51 dB m 2 at zero degree) in practical applications. Therefore, it is believed that the as-prepared Fe3 S4 @C hybrids can be one of the prospective candidates as high-efficiency EMW absorbers. Graphical abstract: Magnetic Fe3 S4 LTMCs micro-flowers@ wax gourd aerogel-derived carbon hybrids as efficient and sustainable electromagnetic absorber. Image 1 Highlights: Magnetic Fe3S4 micro-flowers/ wax gourd aerogel-derived carbon composites were prepared. A RLmin of −58.85 dB and a broad EBW of 5.40 GHz with 20 wt% filling ratio were achieved. Radar cross section simulation confirmed that the material can effectively suppress EMW.